Dependence of Purple Membrane Bump Curvature on pH and Ionic Strength Analyzed Using Atomic Force Microscopy Combined with Solvent Exchange - Yokoyama, Yasunori; Yamada, Kosuke; Higashi, Yosuke; Ozaki, Satoshi; Wang, Haorang; Koito, Naoki; Watanabe, Naoya; Sonoyama, Masashi; Mitaku, Shigeki (The journal of physical chemistry. B, 2014)
Purple membrane (PM), which is a membrane patch formed by the self-assembly of the membrane protein bacteriorhodopsin (bR) with archaeal lipids, is a good subject for studying the mechanism for the supramolecular structural formation of membrane proteins. Several studies have suggested that PM is not simply planar but that it has a curvature. Atomic force microscopy (AFM) studies also indicate the presence of dome-like structures (bumps) on the cytoplasmic surface of PM. PM must have a curvature to form the bump structures; therefore, bump formations will be related to a mechanism for supramolecular structural formation via self-assembly. To elucidate the effect of an asymmetric distribution of charged residues between two aqueous domains on the bump curvature, AFM topography of identical PM sheets were examined with variation of the solvent ionic strength and pH using a newly constructed solvent circulation system. The radius and height distributions of the bumps on the identical PM sheets indicated a linear correlation. The bump curvature, which was simply estimated by the slope of the distribution, became smaller with increasing KCl concentration, which suggests that tension at the cytoplasmic surface caused by electrostatic repulsive force between negatively charged amino acid residues becomes weaker by the electrostatic shielding effect. AFM observations revealed that the bump curvature remained even at high KCl concentration where the Debye length is within a few Angstroms; therefore, the contribution of the intrinsic difference between the domain sizes of bR between two sides was confirmed. Interestingly, the bump curvature was significantly increased by the addition of CaCl2 and then decreased with a similar dependency to KCl at higher CaCl2 concentration. The effect of pH on the bump curvature was also examined, where the curvature increased and reached a maximum at pH 9, while it decreased above pH 10, at which point the two-dimensional crystalline lattice of bR began to disassemble. These experimental results indicate that the bump curvature is strongly influenced by electrostatic interactions. A plausible model for bump structure formation by electrostatic repulsive force is presented based on these results.